Evaluation of Water Quality Based on Macrozoobenthos as a Bioindicator in the Four Springs of Wana Wiyata Widya Karya Tourism Area, Cowek Village, Purwodadi District, Pasuruan Regency - Mas Khoirud Darojat; Nia Kurniawan; Catur Retnaningdyah (Journal of Indonesian Tourism and Development Studies, 2020)
The purpose of this study was to determine water quality based on the physicochemical of water and biotic indices from macrozoobenthos in four springs in the Wana Wiyata Widya Karya tourism area, Cowek Village, Pasuruan. Â Identification and calculation of macrozoobenthos were used to determine the macrozoobenthos community structure and some biotic indices (ASPT, FBI, EPT indices, and water quality index) as bioindicators of water quality. Water quality grouping based on physicochemical of water and biotic indices was analyzed using Cluster Analysis, and Biplot. The results showed that several physical-chemical parameters of water observed had values exceeding water quality standards for drinking water raw materials (BOD, DO, temperature and pH), based on Government Regulations No. 82 of 2001. Based on the NSF-Water Quality Index, water quality in four springs in the Wana Wiyata Widya Karya tourism area is in good category (72.77-88.37), which indicates that the waters are not contaminated with organic matter. Water quality based on the macrozoobenthos diversity index value indicates the category of moderate to mild contamination (H value 1.40-1.97). The Bray-Curtis similarity index resulted in a high level of similarity between of Alang-Alang and Sumber Bendo in 86.49%.Keywords: biotic index, macrozoobenthos, springs, Wana Wiyata Widya Karya, water quality